An increase in the cerebral infarction area during fatigue is mediated by il-6 through an induction of fibrinogen synthesis - Lei, Hong (2014)
OBJECTIVES: Our study aimed to investigate the impact of fatigue on the severity of stroke and to explore the underlying mechanisms. METHODS: Fatigued male rats underwent middle cerebral artery occlusion and the infarcted brain area was determined. Then, coagulation parameters were assessed in the fatigued group and a control group. In addition, the level of fibrinogen was determined in rats deprived of sleep for various numbers of days. To study whether interleukin-6 was involved in fibrinogen synthesis during fatigue, we also measured levels of interleukin-6 in rats deprived of sleep for various numbers of days. Furthermore, brain injury by middle cerebral artery occlusion was measured in wild-type mice, interleukin-6-/- mice and wild-type mice treated with bezafibrate. RESULTS: More severe cerebral infarction was observed in the fatigued rats, resulting in an infarct ratio of 23.4%. The infarct ratio was significantly increased in the fatigued rats compared with that in the control group (8%, p